Pengaruh Laba Akuntansi, Nilai Buku Ekuitas, dan Total Arus Kas terhadap Harga Saham (Studi Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Fitri, Raisa; Aisjah, Siti; Djazuli, Atim (Universitas Brawijaya, Indonesia, 2016)
The capital market has been provided with abundant information available to the investor. Information represents a fundamental demand to the investor in the decision making. The published information will convince the investors. In this study, the parameteres used to measure the perfomance of company based on financial statments is earning, book value of equity, and total cash flow. This study aims to examine and analyze the effect of variable Earning, Book Value of Equity and Total Cash Flow on Stock Price, using a quantitative approach with the method of Regression Analysis Regression. The population of this study is manufacturing companies listed in Indonesia Stock Exchange that has a profit during the study period 2006-2012. The number of population are 52 companies that are observed within 7 years, in order to obtain a total of 364 observations. The results shows that the earning variables provide information and useful in the assessment of the securities, the larger an enterprise earning, then there is the trend of the higher stock prices, while the book value equity variable has a negative effect on stock prices. If the book value of equity increases, then the stock price will decrease. Investors do not use the equity book value as information that needs to be considered in decisions to invest when the company's activity gain a profit. Variable total cash flow has a positive effect on stock prices. If the higher total cash flow will increase the stock price, then it means that the total increase in cash flow will be followed by a rise in stock prices.